PENYEBARAN JENIS TIKUS DI KEBUN RAYA BOGOR - TAPPA, B.; ADISOEMARTO, S. (BERITA BIOLOGI, 1985)
B. TAPPA & S. ADISOEMARTO. 1985. Rat distribution in the Bogor Botanic Garden. Berita Biologi 3 (1) : 5 - 7. A study on rat distribution in the Bogor Botanical Garden was conducted in dry and wet season for one year period. Live-trapping was placed at habitat ten types. Three rats species were recorded during the study, i.e. Rattus tiomanicus, R.r. diardii and R. exulans. R. tiomanicus was found to be the most predominant species and its population more abundant than R.r. diardii and R. exulans. R. tiomanicus typically was captured at trap stations characterized by bamboo clumps, bananas and palms vegetation. R.r. diardii generally was trapped at stations with block housing area. R. exulans occupied may occur on some types of habitat.Analysis of rat distribution related trapping period wa s als o discussed